THE ROLE OF THE ISLAMIC RELIGION IN ARCHITECTURE (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article describes the role of religion in the creation of architecture, the creation of a new style of Islam in architecture, answers to the question "What is a theory?", As well as the stages of studying the theory of Islamic architecture.